PHYSICAL–CHEMICAL AND SENSORY ATTRIBUTES OF THE COCOA NACIONAL (Theobroma cacao L.) FIFTEEN CLONE BEANS IN ECUADOR - Vera Chang, Jaime Fabian (2015)
This research was carried out at La Represa Experimental Farm, property of the State Technical University of Quevedo and at the Cocoa Quality Lab, belonging to EET-Pichilingue-INIAP for a period of four months (February–January 2013). The objective was to characterize the physical – chemical attributes of beans and sensory attributes of paste /pasta in fifteen clones of cocoa, being twelve of type Nacional and three  witnesses (batons) (CCN-51, EET-103 e IMC-67). A completely randomized design with three repetitions was used. The studied variables were: seed and cob index, number of beans, 100 seed weight, head pH and percentage. For chemical evaluation fat, energy, and ash were registered. Sensory attributes (flavors, acidity, bitterness, astringency, and sweetness; cocoa, floral, fruits, nuts, and other flavors were evaluated using a 0 to 5 ordinal scale, besides raw/green and mold defects. Principal Components Analysis was made. The highest cob index was shown by DIRCYT-C129 (34.36 g); DIRCYT-C103 showed higher seed index (1.65 g.), concerning the 100 seed weight and fat content, no significant differences (p>0.05) were found, although CCN–51 was a little higher (41.44%).  Concerning physical attributes, clones EET-103, CCN-51 y IMC-67 were better. All the clones showed similar chemical characteristics. DIRCYT-C225 presented the best sensory profile “Arriba or floral flavor” with high potentiality for chocolate industry.